Attitude of Patients Admitted to Internal Diseases Polyclinic towards Conventional and Complementary Medicine and the Affecting Factors - Özer, Zülfünaz; Turan, Gülcan Bahçecioğlu; Bakır, Emine (Sağlık Bilimleri Üniversitesi, 2020)
Aim: This study was done to investigate the attitude of patients admitted to internal disease polyclinic towards conventional and complementary medicine (CCM) and the affecting factors. Method: this cross-sectional descriptive study included 92 individuals admitted to internal disease polyclinic of a private hospital between May-July 2019 who accepted to participate in the study. Data were collected by personal information form and Complementary, Alternative and Conventional Medicine Attitude Scale (CACMAS). Findings: The average age of participants was 41.76±15.27, 73.9% were female, 67.4% were married, 80,4% were Turkish citizen, 44.6% had bachelor’s degree, 35.9% were worker and 62% had no chronic disease. It was determined that 56.5% of the participants used CCM methods, 59.8% stated that they can suggest CMM methods, 66.3% stated that they can quit the treatment when they are using CCM methods, 52.2% stated they would not inform the health personnel about the CMM method they would use and 50% reasoned not informing behavior as the fear that they would receive negative reaction. Total score average of CACMAS scale was 115.78±18.81, total score average of philosophical congruence with complementary medicine was 35.54±8.81, total score average of dissatisfaction with modern medicine was 35.54±10.28, total score average of holistic congruence with health was 44.7±8.25. Conclusions: CCM attitudes of participants were found to be positive and in moderate level. Besides, education, income level, medicine use and knowledge level on CCM affected their attitude towards CCM.

Amaç: Araştırma dahiliye polikliniğine başvuran hastaların geleneksel ve tamamlayıcı tıbba (GETAT) karşı tutumlarını ve etkileyen faktörleri incelemek amacıyla yapıldı. Gereç ve Yöntemler: : Kesitsel tanımlayıcı tipte olan araştırma, Mayıs-Temmuz 2019 tarihleri arasında özel bir hastanenin dahiliye polikliniğine başvuran ve araştırmaya katılmayı kabul eden 92 birey ile yapıldı. Veriler kişisel bilgi formu ve Geleneksel ve Tamamlayıcı Tıp Tutum Ölçeği (CACMAS) ile toplandı. Bulgular: Yaş ortalaması 41,76±15,27 olan bireylerin %73,9’u kadın, %67,4’ü evli, %80,4’ü Türk vatandaşı, %44,6’sı üniversite mezunu, %35,9’u işçi olarak çalışmakta ve %62’sinin herhangi bir kronik hastalığı bulunmamaktadır; Katılımcıların %56,5’i GETAT yöntemlerini kullandığı, %59,8’i GETAT yöntemlerini önerebileceğini, %66,3’ü GETAT yöntemlerini kullanırken tedaviyi bırakabileceğini, %52,2’sikullanacağı GETAT yöntemini sağlık personeline söylemeyeceğini ve söylememe nedeni olarak ise %50’sinin olumsuz tepki almaktan korkması olduğu belirlendi. CACMAS ölçek toplam puan ortalaması 115,78±18,81, tamamlayıcı tıbba düşünsel bakış toplam puan ortalaması 35,54±8,81, modern tıbba karşı memnuniyetsizlik toplam puan ortalaması 35,54±10,28, sağlığa bütüncül bakış toplam puan ortalaması ise 44,7±8,25 bulundu. Sonuç: Katılımcıların GETAT’a yönelik tutumlarının pozitif ve orta düzeyde olduğu belirlendi. Ayrıca katılımcıların eğitim durumu, gelir seviyesi, ilaç kullanımı ve GETAT hakkındaki bilgi durumu GETAT’a karşı tutumlarını etkilemektedir.
Dahiliye Polikliniğine Başvuran Hastaların Geleneksel ve Tamamlayıcı Tıbba Karşı Tutumları ve Etkileyen Faktörler
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi